FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI SALAK DALAM MEMILIH SALURAN PEMASARAN - Harahap, Juraidah; Sriyoto, Sriyoto; Yuliarti, Ellys (Jurnal AGRISEP, 2018)
The purpose of this study was to determine the pattern of the decision of farmers about salak in choosing the marketing channel and what factors influence what is done by salak farmers in choosing the marketing channel in Parsalakan village, West Angkola District, South Tapanuli District. North Sumatra. Based on the results of research, decision-making pattern of salak farmers in choosing marketing channel is dominated by husband and wife team roles are equal. While the results of statistical analysis of farming experience provide a significant effect on the decision of farmers. While age, cash requirement, length of formal education, distance, the number of dependents of the family and the area of land partially do not give a significant effect on the decision of farmers in choosing marketing channels.